INTERACTION BETWEEN ENERGY CONSUMPTION AND ECONOMIC GROWTH IN INDIA - Nandakumar; Devasia; Thomachan (International Journal of Research -GRANTHAALAYAH, 2017)
This Paper examines the relation between energy use and GDP percapita of India. It used the annual data from 1971-2013, obtained from World Development Indicators of World Bank for India. The variables used in this study are – Percapita GDP and Energy consumption in Kilograms of oil equivalent (Kgoe). The result shows long run relation between energy use and GDP percapita. The result also shows that Energy Use granger causes GDP percapita of India for the sample period.